EXPLORING THE PROFILE OF SCIENTIFIC ARTICLE WRITING ABILITY AMONG TERTIARY STUDENTS: INSIGHTS FROM FIVE INSTITUTIONS IN INDONESIA - Hernawan, Hernawan; Anshari, Dadang; Syihabuddin, Syihabuddin; Mulyati, Yeti (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2023)
The motivation for this study stems from the observation that the culture and ability of tertiary students to write scientific articles are at a low level. This study aims to describe the profile of students’ scientific writing abilities. A descriptive method was used to gather data from five tertiary institutions in West Java. This study used a qualitative approach. The samples included 5 lecturers and 211 students. Data were collected using student needs questionnaires, interviews with lecturers, and analysis of student scientific articles. Data collection techniques included questionnaires and interviews and were analyzed using descriptive data analysis. The findings indicate that students’ ability to write scientific articles falls within the sufficient category. Despite this reality, the questionnaire results reveal that students still encounter difficulties in writing scientific articles and require a learning model that makes the process easier and helps to overcome problems in writing. The analysis of interviews with lecturers of scientific writing courses suggests that students’ ability to write scientific papers is adequate. Lecturers have implemented various learning methods during lectures because not all students like writing scientific articles. Moreover, most students are still confused about writing scientific articles correctly, and their motivation to read is low.